Caravel meshes: A new geometrical strategy to rationalize curved envelopes. (December 2020) - Tellier, Xavier; Douthe, Cyril; Hauswirth, Laurent; Baverel, Olivier
Abstract: Curved structural envelopes have been popular in architecture in the past decades. Their main limitation is their high cost, which is due in particular to the manufacturing complexity induced by curvature. This article introduces Caravel meshes, a new family of meshes that offers geometrical properties allowing a significant reduction of fabrication complexity. In particular, for gridshells, the most complicated fabrication aspect is usually the connection between the structural elements – beams and panels. In Caravel meshes, all these connections are rationalized. Beams are connected to panels without kinks, beams are connected top each other with repetitive which are also free of geometrical torsion. We show that a great variety of mesh combinatorics is possible with these properties. We study in particular quadrangular and hexagonal patterns. In each case, we estimate the possible shapes using differential geometry. We show that hexagonal Caravel meshes offer a significant design freedom, such that other geometrical properties simplifying fabrication can be obtained, such as edge offsets. Finally, we show that Caravel meshes offer many new ways to design curved structural systems, in which beams and panels may work together mechanically. We highlight one application for the fast prototyping of curved surfaces.